Losing stinks! The effect of competition outcome on body odour quality - Fialová, Jitka; Třebický, Vít; Kuba, Radim; Stella, David; Binter, Jakub; Havlíček, Jan (Philosophical transactions of the Royal Society of London. Series B, Biological sciences, 2020)
Dominance hierarchy is often established via repeated agonistic encounters where consistent winners are considered dominant. Human body odour contains cues to psychological dominance and competition, but it is not known whether competition outcome (a marker of a change in dominance hierarchy) affects the hedonic quality of human axillary odour. Therefore, we investigated the effect of winning and losing on odour quality. We collected odour samples from Mixed Martial Arts fighters approximately 1 h before and immediately after a match. Raters then assessed samples for pleasantness, attractiveness, masculinity and intensity. We also obtained data on donors' affective state and cortisol and testosterone levels, since these are known to be associated with competition and body odour quality. Perceived body odour pleasantness, attractiveness and intensity significantly decreased while masculinity increased after a match irrespective of the outcome. Nonetheless, losing a match affected the pleasantness of body odour more profoundly, though bordering formal level of significance. Moreover, a path analysis revealed that match loss led to a decrease in odour attractiveness, which was mediated by participants' negative affective states. Our study suggests that physical competition and to some extent also its outcome affect the perceived quality of human body odour in specific real-life settings, thus providing cues to dominance-related characteristics. This article is part of the Theo Murphy meeting issue 'Olfactory communication in humans'.
Keywords: bojové sporty; Olfactory Perception; Odorants; Smell; Česká republika; testosterone; cortisol; mužské pohlaví; olfaction; Testosterone; Adult; mladý dospělý; Czech Republic; dominance; testosteron; hydrokortison; Young Adult; čichová percepce; Hydrocortisone; Humans; Martial Arts; kompetitivní chování; smell; čich; dospělí; Competitive Behavior; odoranty; lidé; Male; hierarchy